The Effect of Audit Committee Characteristics on Firm Performance: Evidence from Non-Financial Sectors in Oman - Shamsuddin, Amanuddin Bin; Alshahri, Ghazi Mohammed (Asian Economic and Financial Review, 2022)
This study aims to observe the effect of audit committee (AC) characteristics, namely AC size (ACS), AC independence (ACI), and AC meetings (ACM) on two financial performance indicators; return on assets (ROA) and Tobin’s Q. This study was conducted on 63 non-financial firms listed on the Muscat Securities Market (MSM) in Oman for the period from 2016 to 2019. Multiple regression techniques have been applied to analyze the data and get empirical results. The findings revealed that two of the three independent variables have an insignificant effect on financial performance, and ACI has a substantial negative effect on Tobin’s Q. Based on the findings, it can be implied that the corporate governance mechanism and AC structure in Omani firms need to be improved. Stricter control government authorities may be necessary to ensure that firms appoint AC members who can enhance the firm’s performance, and contribute to the country’s economic expansion.